USING SIGIL TO MAKE AN ELECTRONIC MODULE AND ITS PRACTICAL VALUE - Jannah Jannah; Kaspul Kaspul; Nurul Hidayati Utami (Universitas Negeri Padang, 2022)
Electronic modules are teaching materials, that arranged systematically, covering competencies that will be mastered by students and equipped with an attractive appearance. Sigil is an e-book maker with an epub output format. This study aims to describe practicality of the electronic module using Sigil application oriented the scientific approach to environmental change materials for high school level. This type of research is Research and Development (R&D) which refers to the 4-D model. 4-D model consist 4 main stages; define, design, develop and disseminate. The subjects in this study were 9 students of SMAN 7 Banjarmasin. The instrument was a questionnaire. The results of practicality test obtained an average percentage of 88.54% (very practical), 88.00% in the display aspect (very good), 92.44% in the material presentation aspect (very good), and 85.18% in the benefits aspect (very good). Overall, it is very practical and can be used by students.